Pengembangan Buku Ajar untuk Menunjang Pembelajaran Kurikulum Merdeka pada Materi Pengenalan Ilmu Kimia Fase E SMA/ MA - Annisa Mardatilla; Okta Suryani; Mawardi (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2023)
This study aims to develop textbooks to support Merdeka Curriculum learning at the topic ‘Introduction of Chemistry’ in E phase, also to determine the validity and level of practicality. The research method that used was Educational Design Research (EDR) through the Plomp’s development model. The data collection instrument were a validity questionnaire and a practicality questionnaire. The results of the validity questionnaire were analyzed with the Aiken's V formula and practicality rated by a modified formula. The results showed that the textbook has developed and proven its validity with an average validity of 0,87 and practical significantly in the small group test for students with an average of practicality 94,05%. Additionally, result from practicality test for teachers got an average number of 94,71%